A Case Study Of Vicharchika W.S.R.To Atopic Dermatitis - Tawde, Kirtibala; Joshi, Prakash; Wane, Yogesh (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is a traditional medical system where all fundamentals about health and normal wellbeing are described. Health is wealth of a human being. Any disturbance in normal lifestyle causes health issues. Skin is a mirror of our body. Any misbalance in internal physiology will be reflected in the skin. All skin disorders occur due to misbalance of any Dosha, Dhatu (body tissue) or Mala (waste). Vicharchika is one of them (one type of Kushtha Roga (skin diseases) and it can be correlated in modern science with atopic dermatits. Aim and objective- in this study Ayurvedic treatment of Vicharchika is described. Material- Ayurvedic Samhita and their commentaries and modern science books published research papers, articles, medical journals and internet are used for the study. Method- Type of study- clinical case study. Results and conclusion- The treatment of Vicharchika through Ayurveda approach is incredible and result seems good. Conclusion will be made.